2014
DOI: 10.1002/hc.21158
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multicyclic Heterocycles Initiated by C–H Bond Activation Along with “Rollover” Using a Rh(III) Catalyst

Abstract: Various multicyclic heterocycles were synthesized via “rollover” as the key pathway using a Rh(III) catalyst with a catalytic amount of sodium pivalate or copper(II) acetate. 3‐Alkynyl‐2‐heteroarylpyridines were transformed into tri‐ or tetracyclic heterocycles containing two heteroatoms via an intramolecular alkyne insertion. 3‐Aryloyl‐2‐arylpyridines were derived into 4‐azafluoren‐9‐ols via the intramolecular carbonyl insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The pyridine core has been used as a directing group in the rhodium(III)‐catalyzed cyclization of 3‐alkenyl‐2‐arylpyridines 75a – j , as reported by Shibata et al (Scheme ) , . The approach, based on the concept of metal “rollover”, afforded 4‐azafluorenes 76a – j as a mixture of Z/E isomers.…”
Section: Intramolecular Coupling With Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyridine core has been used as a directing group in the rhodium(III)‐catalyzed cyclization of 3‐alkenyl‐2‐arylpyridines 75a – j , as reported by Shibata et al (Scheme ) , . The approach, based on the concept of metal “rollover”, afforded 4‐azafluorenes 76a – j as a mixture of Z/E isomers.…”
Section: Intramolecular Coupling With Alkynesmentioning
confidence: 99%
“…In connection with their work on the synthesis of 4‐azafluorenes by C–H activation involving a “ rollover “ process, the group of Shibata investigated carbonyl groups as coupling partners (Scheme ) . Treatment of 3‐aryloyl‐2‐arylpyridines 100a – e with catalytic amount of Rh III dimer ([Cp*RhCl 2 ] 2 ) and PivONa afforded tertiary alcohols 101a – e .…”
Section: Intramolecular Coupling With Carbonyl and Azide Derivativesmentioning
confidence: 99%
“…The rollover process has received growing interest in recent years with potential applications in organic synthesis, mediated by Pt(II) 26 and Pd(II) 27 complexes, and very recently, in homogeneous catalysis, with a series of different processes promoted by Pd(II), 28 Rh(III) 29 and Ru(II). …”
Section: Rollover Cyclometalationmentioning
confidence: 99%
“…Furthermore, the analogous reaction of 3-aryloyl-2-arylpyridines gave 7-substituted 4-azafluoren-9-ols. In order to prove the role of the pyridine nitrogen atom in the process, the authors showed that no reaction proceeded starting from nitrogen-free analogues, or positional isomers, not able to assist C–H bond cleavage and the subsequent rollover process [ 152 ].…”
Section: Catalysismentioning
confidence: 99%